2011
DOI: 10.1007/s00296-011-2066-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of bone mineral density with disease activity and functional ability in patients with ankylosing spondylitis: a cross-sectional study

Abstract: SummaryAim. In ankylosing spondylitis (AS) inflammatory activity probably plays a key role in the pathophysiology of bone loss. The aim of the study was to investigate the relationship of bone mineral density (BMD) at the lumbar spine and hip region with some measures of disease activity and functional ability in patients with ankylosing spondylitis.Methods: In 80 patients with established ankylosing spondylitis disease activity and functional ability were determined by C-reactive protein (CRP), erythrocyte se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 30 publications
2
9
0
1
Order By: Relevance
“…Bone marrow edema in AS patients is related to inflammation, which leads to increased water in extracellular spaces and may indicate that the increase of disease activity states causes an increase in the diffusion of local water molecules, resulting in higher ADC mean values . Previous studies have reported that low bone marrow density is correlated with high disease activity in AS patients with increased ADC values, which is in agreement with our results …”
Section: Discussionsupporting
confidence: 92%
“…Bone marrow edema in AS patients is related to inflammation, which leads to increased water in extracellular spaces and may indicate that the increase of disease activity states causes an increase in the diffusion of local water molecules, resulting in higher ADC mean values . Previous studies have reported that low bone marrow density is correlated with high disease activity in AS patients with increased ADC values, which is in agreement with our results …”
Section: Discussionsupporting
confidence: 92%
“…Perhaps, BMD measurement at the FN is not affected by the syndesmophytes and ectopic calcifications that frequently occur in the LS [36,37]. Previous studies obtained similar findings and showed that anteroposterior lumbar DXA results could be misleading when evaluating the extent of OP and treating late-stage-AS patients [38,39]. Table 1 for definitions a Significant difference from the control group b Significant difference from the normal BMD group c Significant difference from the osteopenia group Table 3 Correlations between BMD T-scores, Table 1 for definitions Results are presented as the coefficient of correlation.…”
Section: Discussionsupporting
confidence: 67%
“…erosions) and new bone formation, the latter being the main radiological characteristic of ankylosing spondylitis [35,36]. In spite of bony growth in ankylosing spondylitis osteoporosis of the lumbar spine was found in up to 34.3% and osteoporosis of the hip in up to 29% patients [37][38][39][40][41][42]. Moreover, Capaci et al found that even 61.6% of patients with mild AS had spinal osteoporosis and osteopenia, while 46.6% had osteoporosis and osteopenia at the total hip [43].…”
Section: Discussionmentioning
confidence: 99%